STRATEGI PENGEMBANGAN FUNGSI TERMINAL PENUMPANG TIPE B DI PROVINSI SULAWESI TENGGARA - Hado Hasina; Maudhy Satyadharma (Journal Publicuho, 2023)
This study aims to describe and analyze (1) the Type B Passenger Terminal function in the Southeast Sulawesi Province and (2) the strategy for developing the function of the Type B Passenger Terminal in the Southeast Sulawesi Province. Data analysis, namely with qualitative descriptive analysis and SWOT analysis. The research was carried out in Kendari City in August - December 2022. The results of the study concluded that (1) the terminal function has not been running optimally and, (2) strategies that must be carried out, namely a) Utilizing the terminal's strategic position by encouraging public transport companies using large terminal land, b) Partnering with private parties in accordance with regulations to utilize large terminal land to build terminal supporting facilities, c) Make effective officers at each terminal to direct drivers and passengers to the terminal and control the shadow terminals that disrupt the function of existing terminals, d) Synergize with city/district government in the synergy of the city/regency route network with the location of the type B passenger terminal and e) Encouraging the improvement of the quality of Transportation Human Resources, especially terminal management so that the implementation and management of the terminal runs according to the specified SOP.